2014
DOI: 10.1002/14651858.cd010844.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Long-acting inhaled therapy (beta-agonists, anticholinergics and steroids) for COPD: a network meta-analysis

Abstract: This network meta-analysis compares four different classes of long-acting inhalers for people with COPD who need more than short-acting bronchodilators. Quality of life and lung function were improved most on combination inhalers (LABA and ICS) and least on ICS alone at 6 and at 12 months. Overall LAMA and LABA inhalers had similar effects, particularly at 12 months. The network has demonstrated the benefit of ICS when added to LABA for these outcomes in participants who largely had an FEV1 that was less than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
49
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(54 citation statements)
references
References 331 publications
1
49
0
4
Order By: Relevance
“…23,24 Our finding that newly identified cases tended to have mild or moderate airflow obstruction was in keeping with previous case-finding studies 10 and newly case-found patients were generally less severe than patients newly diagnosed in primary care. 25 Nevertheless, in accordance with our model, the majority of new cases could potentially benefit from inhalers, 26,27 self-management support, 28 smoking cessation 29 and vaccinations. 30 A substantial proportion (27%) also had significant breathlessness with potential to benefit from pulmonary rehabilitation.…”
supporting
confidence: 70%
“…23,24 Our finding that newly identified cases tended to have mild or moderate airflow obstruction was in keeping with previous case-finding studies 10 and newly case-found patients were generally less severe than patients newly diagnosed in primary care. 25 Nevertheless, in accordance with our model, the majority of new cases could potentially benefit from inhalers, 26,27 self-management support, 28 smoking cessation 29 and vaccinations. 30 A substantial proportion (27%) also had significant breathlessness with potential to benefit from pulmonary rehabilitation.…”
supporting
confidence: 70%
“…This effect may also be present in COPD airways, given that ~30% of CFTR function remains [15, 137, 161]. Similarly, inhaled 2 adrenergic receptor agonists are a mainstay of COPD treatment, and they are thought to relieve the airway obstruction by inducing smooth muscle relaxation, as seen in asthmatic patients [216]. However, these agonists also activate CFTR [217].…”
Section: Treatment For Cftr Diminution and Mucus Dehydration In Copdmentioning
confidence: 99%
“…Lastly, a new Cochrane network meta-analysis demonstrated that within the available evidence, ICS/LABA shows the biggest improvements compared with placebo, followed by LAMA or LABA, and then ICS alone, for both the SGRQ and FEV1 values [22]. They did not analyse other clinically important outcomes such as mortality and exacerbations, quoting two other meta-analyses on these instead: Dong et al [23] found that ICS/LABA had the lowest risk of mortality when compared with placebo, tiotropium or LABA only, and a 2009 meta-analysis looking at exacerbations only, which found that neither ICS or ICS/LABA was more effective than each other or LAMA [24].…”
Section: Stable Copd: Inhaled Corticosteroidsmentioning
confidence: 99%